Notes on certain analytic functions - Owa, Shigeyoshi; YAVUZ, EMEL (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY-TUBITAK, ATATURK BULVARI NO 221, KAVAKLIDERE, TR-06100 ANKARA, TURKEY, 2019)
Let A(n) be the class of functions f(z) = a(n)z(n) + a(n+1)z(n+1) +...(n is an element of N), which are analytic in the open unit disk U, where a(n) not equal 0. For f(z) is an element of A(n), Miller and Mocanu in 1978 showed a very interesting result for f(z). Applying the result due to Miller and Mocanu, we would like to consider some new results for such functions. Our results in this paper are generalizations for results by Nunokawa in 1992.
Keywords: Analytic Function; The Class S(n,alpha); The Class K(n,alpha)